Efeito conjunto de sinais interferentes e ruído em canais Wiretap com múltiplas antenas e atraso de feedback - Ortega, Yosbel Rodríguez (2017)
In this dissertation, the physical layer security of wiretap channels with multiple antennas and outdated channel state information (CSI) at the transmitter is investigated in terms of the secrecy outage probability. The joint effect of multiple jamming signals and noise at the eavesdropper is studied. In parallel, it is analyzed the special case where only the transmitter is equipped with multiple antennas. On such models, the transmitter employs a transmit antenna selection (TAS) technique; the legitimate receiver uses either a selection combining (SC) or a maximal-ratio combining (MRC) scheme; and the eavesdropper adopts the MRC technique. Exact closed-form expressions for the non-zero secrecy rate and secrecy outage probability for arbitrary number of power distributed jamming signals are derived, by assuming both perfect and imperfect CSI. The attained expressions are simplified for two special cases: distinct and equal power distributed jamming signals. An asymptotic secrecy outage analysis is conducted, which shows that the expected diversity gain cannot be realized for imperfect CSI, and full diversity order can only be achieved under perfect CSI condition. In addition, those results reveal that the number of jamming signals as well as the number of antennas at the eavesdropper do not affect the system diversity order. Representative numerical examples are presented to illustrate the effects of the key system parameters on the secrecy outage performance. Finally, the proposed analysis is validated through Monte Carlo simulation results.